Epidemiology of arboviruses in humans and livestock in Ethiopia: a systematic review and meta-analysis - Alemu Gedefie; Habtu Debash; Altaseb Beyene Kassaw; Gossa Mankelkl; Yeshi Metaferia; Melaku Ashagrie Belete; Sisay Desale; Saleamlak Sebsibe; Mihret Tilahun; Bruktawit Eshetu; Agumas Shibabaw; Yeshimebet Kassa; et al. (BMC Infectious Diseases)
Abstract Background Arbovirus infections are a global public health threat, accounting for approximately 73% of the total emerging and re-emerging human infections, where the burden is worsened in sub-Saharan Africa, including Ethiopia. However, the surveillance system has been still challenged, and their burden and magnitude are not well estimated due to underestimates of true arbovirus burdens by passive case detections. To support targeted evidence-based public health decision-making, comprehensive evidence of arbovirus prevalence is crucial. Thus, the aim of this study was to assess the prevalence of arboviruses in humans and livestock in Ethiopia. Method Articles were extensively searched in bibliographic databases and gray literatures using entry terms or phrases. PRISMA 2020 flow diagram was used and data among studies meeting eligibility criteria extracted in MS Excel sheet and exported into STATA-17 software for analysis. A random-effects model was used to compute the pooled magnitude of arboviruses in humans and livestock. The heterogeneity was quantified using the I2 value. Publication bias was assessed using a funnel plot and Egger’s test. Sensitivity analysis, subgroup analysis and meta-regression were performed to explore heterogeneity. Result Of the 1957 studies identified, 39 human and 6 livestock studies were eligible for meta-analysis. The overall pooled sero-epidemiology of arboviruses in humans using anti-IgG and anti-IgM was 15.43% (95% CI: 12.11-18.76) and 10.04% (95% CI: 6.46-13.62), respectively. The molecular prevalence of arboviruses in humans was 38.42% (95% CI: 21.77-55.08). The pooled prevalence of arboviruses in livestock was 15.77% (95% CI: 0.45, 31.08). Dengue virus, Yellow fever virus, Zika virus, Rift valley fever, West Nile virus, and chikungunya virus in humans and Rift valley fever, West Nile virus, and Schmallenberg virus in livestock were reported. Conclusion The magnitude of arboviruses in humans and livestock in Ethiopia alarms the need for immediate multi-sectoral interventions such as strengthening laboratory diagnostic capacities, undertaking an integrated regular national surveillance, and implementation of one-health initiatives and a planetary health approach.